Distribution Flow Overview of Medicine and Medical Devices at X Purwodadi Hospital - Fransisca Michelline Tuwanakotta; Yulia Pratiwi; Yanulia Handayani; Mera Putri Pratitis; Aprillia Puspitasari Tunggadewi; Wildayanti Wildayanti (International Journal Of Health Science, 2025)
Pharmacy services in a hospital support quality health services. Distribution is a crucial aspect of hospital pharmacy services, which aims to ensure the timely availability of pharmaceutical supplies within the unit. The purpose of this study was to determine the alignment of distribution procedures at X Hospital with the Standard Operating Procedure (SOP) and Permenkes No. 72 of 2016. This study was non-experimental with a qualitative descriptive method with a total sampling technique. The instruments used in this study were checklist sheets, interview guidelines, hospital SOP, and Permenkes No. 72 of 2016. The implementation of the study was through observation, document review, and in-depth interviews with all pharmacy employees at X Hospital. Interviews were conducted with 1 key informant, 8 informants in the pharmacy warehouse section, and 29 informants in the inpatient and outpatient services sections. Data obtained from the checklist results were processed using Microsoft Excel, and the results of the interviews were transcribed and interpreted. Based on the results of interviews and observations, it was shown that the implementation of distribution refers to the hospital SOP. The distribution system used is a centralized system and UDD (Unit Dose Dispensing) for inpatients. The results of the study also showed the percentage of conformity of the distribution process with the hospital SOP of 86.8% and conformity of distribution with Permenkes No. 72 of 2016 of 66.59%.